Descriptive study of Venous Thromboembolic Disease in the adult population admitted to Tshepong Hospital comparing the proportion of HIV and non-HIV infected patients - Moodley, Pramodhini (My University, 2019)
Background HIV and TB independently incur increased risk for venous thromboembolic disease (VTE): deep vein thrombosis (DVT) and/or pulmonary embolism (PE). Data from high HIV and TB burden settings describing VTE is scarce. The Wells’ DVT and PE scores are widely used but their utility in these settings has not been reported on extensively. We therefore report clinical and treatment aspects of in-patients with newly diagnosed VTE to assess HIV and TB prevalence, and their Wells’ score. Setting Tshepong Hospital in the North West Province of South Africa. Methods A prospective cohort of adult in-patients with radiologically confirmed VTE were recruited. Demographics, presence of TB, HIV status, duration of treatment, CD4 count, viral load, VTE risk factors, and parameters to calculate the Wells’ score were collected. Results One hundred patients were recruited, of whom 59 were HIV-infected; 39 had TB disease and 32 were HIV/TB co-infected. Eighty -three patients had a DVT only; 11 patients had a PE, and six had both a DVT and PE. Eighteen of 42 patients on antiretroviral treatment (ART) were on treatment for less than six months. Twenty patients of 39 were on TB treatment for less than one month. The median DVT and PE Wells’ score in all sub-groups was 3.0 (IQR: 1.0-4.0) and 3.0 (IQR: 2.5-4.5), respectively. There were nine deaths. Conclusion HIV /TB co-infection appear to confer a risk for VTE, especially early after ART and/or TB treatment, and therefore require careful monitoring for VTE and early initiation of thrombo-prophylaxis.
A research report submitted to the University of Witwatersrand, Johannesburg in fulfilment for the requirements of the degree of Master of Medicine 4 June 2019 Descriptive study of Venous Thromboembolic Disease in the adult population admitted to Tshepong Hospital comparing the proportion of HIV and non-HIV infected patients
Keywords: Thrombosis; Thromboembolism--Prevention--Control Embolism